Percutaneous Gastrostomy Tube Placement: Recognizing When Things Go Wrong - Hoang, Peter T.; Menias, Christine O.; Niemeyer, Matthew M. (Seminars in Interventional Radiology, 2019)
Percutaneous radiologic gastrostomy is a commonly performed, minimally invasive procedure for long-term enteral access in patients with a variety of conditions. Compared with other methods, it is less invasive, less costly, and safe, with a high technical success rate. The risk of complications is low, and most require only conservative management. Early, accurate diagnosis of more severe complication is crucial, as these may require prompt intervention. Therefore, radiologists should understand the imaging features, clinical presentation, and management of gastrostomy-related complications. This article will review the indications for long-term enteral access, discuss the available methods, summarize the percutaneous radiologic technique, and highlight the associated complications from gastrostomy placement.
Keywords: drainage; gastrostomy; interventional radiology; surgical interventions